2020
DOI: 10.1002/cche.10296
|View full text |Cite
|
Sign up to set email alerts
|

Frost‐affected lentil (Lens culinaris M.) compositional changes through extrusion: Potential application for the food industry

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
5
0
2
Order By: Relevance
“…Although there is not a recommended daily intake of galactosides, the consumption of up to 3 g/day of galactosides can provide health effects without provoking flatulence discomfort [ 32 ]; then, considering one serving of 40 g, the snacks elaborated can supply from 0.6 g (CE) to 0.32 g (EF#5). Other authors have confirmed that extrusion cooking results in an increase of total α-galactoside content in different formulations based on lentil flours [ 2 , 4 ], but it has been also reported that extrusion did not affect the concentration of raffinose, stachyose, or verbascose in wheat–lentil flours [ 30 ]. Indeed, controversy exists about the effect of extrusion on α-galactosides [ 29 ], as it could be dependent on the variety of the pulse and the extrusion conditions.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Although there is not a recommended daily intake of galactosides, the consumption of up to 3 g/day of galactosides can provide health effects without provoking flatulence discomfort [ 32 ]; then, considering one serving of 40 g, the snacks elaborated can supply from 0.6 g (CE) to 0.32 g (EF#5). Other authors have confirmed that extrusion cooking results in an increase of total α-galactoside content in different formulations based on lentil flours [ 2 , 4 ], but it has been also reported that extrusion did not affect the concentration of raffinose, stachyose, or verbascose in wheat–lentil flours [ 30 ]. Indeed, controversy exists about the effect of extrusion on α-galactosides [ 29 ], as it could be dependent on the variety of the pulse and the extrusion conditions.…”
Section: Resultsmentioning
confidence: 87%
“…They reported values of sucrose lower than those found in the present study in both raw and extruded bean flours [ 29 ]. Other authors have reported that the concentration of sucrose was not altered after the extrusion processing of wheat–lentil flours [ 30 ]. However, a decrease in the content of sucrose was reported by Ciudad-Mulero et al (2020b) in extruded flours formulated with lentil and nutritional yeast [ 2 ] and also in extruded flours of chickpea formulations [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another recent study, Portman et al 10 investigated the nutritional profile of premium quality (grade1) and downgraded frost-affected lentils ( Lens culinaris M.) to be used as ingredients in extruded foods. The reasoning behind the use of frost-damaged lentils was that the visual appearance of seeds would not be an essential quality parameter if the seeds were going to be used for protein extraction or production of novel food ingredients.…”
Section: Extraction and Characterization Of Protein Ingredients From ...mentioning
confidence: 99%
“…Similar to puffed popcorn, the variety is important, with notable puffing variety yielding around 50% puffing with 0.6 to 2.1 ml/g expansion and other varieties yield as low as 7% (Mukhopadhyay et al., 2015). Extrusion of pulse flour and cereal blends has been shown to result in puffing to varying extents (Portman et al., 2020; Simons et al., 2015). In contrast, puffing has not been widely reported for pulse flakes (Gupta & Bhattacharya, 2017).…”
Section: Influence Of Materials and Processing On Flake Attributesmentioning
confidence: 99%